Initial foot contact and related kinematics affect impact loading rate in running - Breine, B.; Malcolm, P.; Van Caekenberghe, I.; Fiers, P.; Frederick, E. C.; De Clercq, D. (Journal of Sports Sciences, 2017)
This study assessed kinematic differences between different foot strike patterns and their relationship with peak vertical instantaneous loading rate (VILR) of the ground reaction force (GRF). Fifty-two runners ran at 3.2 m · s-1 while we recorded GRF and lower limb kinematics and determined foot strike pattern: Typical or Atypical rearfoot strike (RFS), midfoot strike (MFS) of forefoot strike (FFS). Typical RFS had longer contact times and a lower leg stiffness than Atypical RFS and MFS. Typical RFS showed a dorsiflexed ankle (7.2 ± 3.5°) and positive foot angle (20.4 ± 4.8°) at initial contact while MFS showed a plantar flexed ankle (-10.4 ± 6.3°) and more horizontal foot (1.6 ± 3.1°). Atypical RFS showed a plantar flexed ankle (-3.1 ± 4.4°) and a small foot angle (7.0 ± 5.1°) at initial contact and had the highest VILR. For the RFS (Typical and Atypical RFS), foot angle at initial contact showed the highest correlation with VILR (r = -0.68). The observed higher VILR in Atypical RFS could be related to both ankle and foot kinematics and global running style that indicate a limited use of known kinematic impact absorbing "strategies" such as initial ankle dorsiflexion in MFS or initial ankle plantar flexion in Typical RFS.